Refractive Index Scaling in Hollow Core Photonic Crystal Fiber - Abbas, Dalya H.; Al-Janabi, Abd-Alhadi M. (Iraqi Journal of Laser, 2019)
In this paper, simulation study of the frequency shift of photonic bandgaps due to refractive index scaling using liquids filled hollow-core photonic crystal fibers is presented. Different liquids (distilled water, n-hexane, methanol, ethanol and acetone) are used to fill the cladding of 2 types of hollow core photonic crystal fibers (HC19-1060, HC7-1060). These liquids are used to change the effective index scaling and index contrast of the cladding. The effect of increasing temperature of the liquid (20-100 0C for water and 20-70 0C for other liquids ) infiltrated hollow core fiber on the bandgap width and transmission properties has been computed. The maximum photonic bandgap width at 0.0243 has appeared with filling HC7-1060 PCF with methanol at 70 0C at a corresponding refractive index 1.3057. Photonic bandgap structure for both TE and TM modes of a 2D photonic crystal with triangular lattice of air holes embedded in silica background material was studied using Plane Wave Expansion (PWE) method to find the width of photonic bandgap finger in photonic crystal states diagram.